Brand origin recognition accuracy: its antecedents and consumers’ cognitive limitations - Samiee, Saeed; Shimp, Terence A; Sharma, Subhash (Journal of International Business Studies, 2005)
An ever-growing literature has reported consumer bias toward national origins of products, and has explored factors that moderate such bias. Researchers have assumed, if only tacitly, that consumers are knowledgeable of brand origins, and that this knowledge is a significant influence that drives judgments of product quality, brand attitudes, and choice behavior in the marketplace. Using categorization theory and attribute diagnosticity as the theoretical foundation, our research reveals that consumers actually have only modest knowledge of the national origins of brands, and that American consumers’ proficiency at recognizing foreign brand origins is predicted by variables such as socioeconomic status, past international travel, foreign language skills, and gender. In the second of two studies, we determined that brand origin recognition is based largely on consumers’ associations of brand names with languages that suggest country origins. These studies ultimately lead us to conclude that past research has inflated the influence that country of origin information has on consumers’ product judgments and behavior and its importance in managerial and public policy decisions.